Flap vs. "flapless" surgical approach at immediate implants: a histomorphometric study in dogs - Caneva, Marco [UNESP]; Botticelli, Daniele; Salata, Luiz Antonio; Scombatti Souza, Sergio Luis; Bressan, Eriberto; Lang, Niklaus P. (Wiley-Blackwell Publishing, Inc, 2010)
AimTo compare the remodeling of the alveolar process at implants installed immediately into extraction sockets by applying a flap or a "flapless" surgical approach in a dog model.Material and methodsImplants were installed immediately into the distal alveoli of the second mandibular premolars of six Labrador dogs. In one side of the mandible, a full-thickness mucoperiosteal flap was elevated (control site), while contra-laterally, the mucosa was gently dislocated, but not elevated (test site) to disclose the alveolar crest. After 4 months of healing, the animals were sacrificed, ground sections were obtained and a histomorphometric analysis was performed.ResultsAfter 4 months of healing, all implants were integrated (n=6). Both at the test and at the control sites, bone resorption occurred with similar outcomes. The buccal bony crest resorption was 1.7 and 1.5 mm at the control and the test sites, respectively.Conclusions"Flapless" implant placement into extraction sockets did not result in the prevention of alveolar bone resorption and did not affect the dimensional changes of the alveolar process following tooth extraction when compared with the usual placement of implants raising mucoperiosteal flaps.To cite this article:Caneva M, Botticelli D, Salata LA, Souza SLS, Bressan E, Lang NP. Flap vs. "flapless" surgical approach at immediate implants: a histomorphometric study in dogs.Clin. Oral Impl. Res. 21, 2010; 1314-1319.doi: 10.1111/j.1600-0501.2009.01959.x.
Keywords: animal study; bone healing; extraction socket; flapless; implant dentistry; osseointegration; socket preservation; surgical approach